2019
DOI: 10.1039/c9ra01233h
|View full text |Cite
|
Sign up to set email alerts
|

Defect structure in δ-Bi5PbY2O11.5

Abstract: Total neutron scattering analysis and ab initio MD simulations reveal details of oxide ion vacancy ordering and migration pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 68 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…There have been many attempts to extend the temperature stability range of the δ-Bi 2 O 3 -like phase to lower temperatures (i.e., lower than 730 °C). Most of them involved solid solutions of Bi 2 O 3 with selected oxides, like Y 2 O 3 [ 70 , 71 ], WO 2 [ 72 ] or others (e.g., [ 73 , 74 ]). Though these solid solutions retained the fluorite structure to temperatures much lower than 730°C, their electrical conductivity was much lower than that of pure δ-Bi 2 O 3 .…”
Section: Extension Of Thermal Stability Range Of High-temperature Phases By Controlled Nanocrystallization Of Glassesmentioning
confidence: 99%
“…There have been many attempts to extend the temperature stability range of the δ-Bi 2 O 3 -like phase to lower temperatures (i.e., lower than 730 °C). Most of them involved solid solutions of Bi 2 O 3 with selected oxides, like Y 2 O 3 [ 70 , 71 ], WO 2 [ 72 ] or others (e.g., [ 73 , 74 ]). Though these solid solutions retained the fluorite structure to temperatures much lower than 730°C, their electrical conductivity was much lower than that of pure δ-Bi 2 O 3 .…”
Section: Extension Of Thermal Stability Range Of High-temperature Phases By Controlled Nanocrystallization Of Glassesmentioning
confidence: 99%
“…We have previously shown that thermally induced changes in conductivity behaviour can be correlated to changes in the oxide ion vacancy distribution in other δ-Bi 2 O 3 type phases [20,38] As seen in other substituted δ-Bi 2 O 3 type phases [20,38,40], the number of tetrahedral site vacancies is significantly greater than that predicted assuming oxide ions are located exclusively within the tetrahedral sites (Table 3). As seen in the crystallographic analysis, there is significant occupancy of the 48i interstitial site, which results in an increase in the tetrahedral site vacancy concentration.…”
Section: Resultsmentioning
confidence: 79%
“…This is in contrast to the situation observed in CeO 2−d , 36 and YDC, 37 where using similar methodology as well as molecular dynamics simulations, a preference for h111i ordering was noted and is more akin to the situation observed in doped bismuth oxide uorites. 53,54 While, the location of a second vacancy in the h100i direction might be thought of as energetically unfavourable due to electrostatic repulsion between the effective positive charges of the vacancies, as discussed above, the results also show evidence of preferred dopant-vacancy association and that the preference for h100i ordering over the random distribution may be associated with the minimisation of local strain around the dopant cation. It should be noted here that the RMC method of analysis does not take into account the energetics of the system, it merely models the physical total scattering data.…”
mentioning
confidence: 64%
“…As previously demonstrated, the expected ratio for randomly distributed h100i, h110i, and h111i aligned vacancy pairs is 1 : 2 : 1.3 in an ideal uorite structure. 53,54 Fig. 4b shows a plot of the partial pair correlation functions for O-O and vacancy-vacancy pairs from the nal RMC congurations for the x = 0.10 composition.…”
mentioning
confidence: 99%